Analysis of maritime team workload and communication dynamics in standard and emergency scenarios - Martin Lochner; Andreas Duenser; Margareta Lützhöft; Ben Brooks; David Rozado (Journal of Shipping and Trade (JST), 2018)
The introduction of next-generation technologies to the maritime shipping industry, including Portable Pilotage Units, Remote Pilotage, advanced situation awareness aids, and Autonomous Shipping, creates an urgent need to understand operator workload during Bridge Team operations, and co-operations with shore based personnel. In this paper we analyse mental workload of maritime Captains, Pilots and Tug Masters during standard and emergency scenarios, using traditional measures (SWAT, ISA), communications analysis, and the collection of simultaneous electro-dermal activity (EDA) of team members. Results indicate that the EDA measure overcomes some of the problems with paper-based techniques, and has excellent temporal resolution for emergency events. Implications for testing of novel technologies are discussed.
Keywords: 650